Comparison of small-scale and large-scale mixing characteristics: Correlations between small-scale and large-scale mixing and extensional characteristics of wheat flour dough - Mann, G.; Diffey, Simon; Allen, H.; Pumpa, J.; Nath, Z.; Morell, M.; Cullis, B.; Smith, A. (2008)
Mixing measurements provide valuable information about dough strength and stability (STAB) traits. These measurements are important in milling and baking operations, and for varietal selection in wheat breeding programmes. There are several techniques with different sample sizes used for measuring these traits so there is interest in examining the agreement between methods in terms of genotypic (varietal) rankings. This issue has been investigated by using two different mixing methods, a small-scale Mixograph (2 g) and large-scale Farinograph (50 g) using data from a doubled haploid population (190 lines) from a Chara (excellent dough strength)×WW2449 (poor dough strength) cross. The cross was grown in a field trial at the Wagga Wagga Agricultural Institute (WWAI) in 2000. Eleven mixing traits were measured and compared according to a statistical design. The estimated genetic correlation matrix for six of the 11 mixing traits, dough development time (DDT), STAB, mixing tolerance index (MTI), maximum bandwidth (MBW), bandwidth at peak resistance (BWPR) and peak resistance (PR) revealed that for these dough-strength-related parameters, both methods were measuring equivalent traits, although individual parameters had widely different coefficients of variation. In this population, PR was correlated with the extensibility trait length determined by large-scale extension testing. None of the large-scale or small-scale mixing traits was an effective predictor of the small-scale extensibility parameter extensibility at Rmax (Ext_Rmax). The data verified that small-scale Mixograph tests are a robust and efficient alternative to large-scale Farinograph tests for both commercial breeding and research. © 2007.